QUO VADIS PERNIKAHAN SAKINAH: MENYOAL BOOMING-NYA TREND PERCERAIAN DI ERA KEKINIAN - Cassandra, Yusi Syamisa; Khamadika, Ratih Latiffah; Hanum, Nurlia; Al Maududi, Abul A’la (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
The rising trend in divorce cases in Indonesia in the last decade reflects a serious challenge to family resilience and a change in marital values. This research explores the Islamic standpoint in analyzing the common causes of divorce and drawing its correlation to the concept of sakinah family, a resilient and harmonious family. This study applies a systematic literature review based on Google Scholar and Garuda (Garba Rujukan Digital) as the database, using the keywords divorce, family resilience, sakinah family, Islamic marriage, and Indonesia. The inclusion criteria covers peer-reviewed articles published between 2021 and 2025 about divorce cases in Indonesia and excludes non-empirical studies, editorial essays, and articles that do not cover Indonesian context, resulting in 26 relevant papers. This study also gathers its secondary data from Indonesian Central Agency of Statistics (BPS) dated back from 2020 to 2024. This study reveals that economic pressure, the spouses’ lack of mental preparedness, early marriage, marital conflict which results in domestic violence, as well as social media influence are among the prominent factors of a divorce. Not only do these factors affect the marriage in general, but also does the divorce affect the children’s mental state, social ability, and education. This study concludes that the gap between the ideal marriage that the concept of sakinah family draws–calm, loving, and harmonious–and the reality of Indonesian modern day marriages are starkly visible. Hence, we strongly recommend the enhancement of premarital education, improving family literacy, as well as the creation of public policy that supports family resilience.